Identification of Bioactive Peptide Inhibitors of Cyclooxygenase-2 from Peanut Worm (Siphonosoma australe): An In Silico Studies - Suwarjoyowirayatno, Suwarjoyowirayatno; Hidayat, Chusnul; Wahyuningsih, Tutik Dwi; Indrati, Retno (Trends in Sciences, 2025)
The study was conducted to address the growing need for safer and more effective anti-inflammatory medications, given the side effects associated with conventional anti-inflammatory drugs. Natural sources, such as bioactive peptides, present a promising alternative. The research aimed to generate cyclooxygenase-2 (COX-2) inhibitory peptides from Siphonosoma australe and evaluate their potential as natural anti-inflammatory drug candidates using in silico methods. The PeptideCutter, SwissADME, SwissTargetPrediction, ToxinPred, and principal component analysis (PCA) were utilised to generate peptides, followed by molecular docking using Yasara-structure software. The study identified 113 peptides as suitable candidates based on their physicochemical properties, COX-2 inhibitory potential, and safety profiles. PCA narrowed these down to 5 peptides; Phenylalanine-Tryptophan (FW), Phenylalanine-Phenylalanine (FF), Phenylalanine-Proline-Phenylalanine (FPF), Leucine-Proline-Phenylalanine (LPF), and Valine-Proline-Phenylalanine (VPF) with similar characteristics to celecoxib. Among these, the FW peptide exhibited the best binding energy (–9.32 kcal/mol) and significant inhibitory interactions with COX-2 through hydrogen bonds with Tyr341 and Val509, hydrophobic interactions with Ile331, Val335, Leu345, Ala502, and Leu517, and plenty of amino acid residues in van der Waals forces. The findings highlight the therapeutic potential of peptides from Siphonosoma australe as natural COX-2 inhibitors, offering a safer alternative to synthetic drugs for managing inflammation. This research contributes to the development of natural anti-inflammatory therapeutics, addressing a critical need in pharmacological research. HIGHLIGHTS Discovery of bioactive peptides from Siphonosoma australe with potential to inhibit COX-2, a key enzyme linked to inflammation, showcasing a natural alternative to synthetic anti-inflammatory drugs. Utilization of in silico methods to rapidly generate and evaluate 503 peptides, reducing time and cost compared to traditional experimental approaches. Advanced bioinformatic tools like PeptideCutter, SwissADME, SwissTargetPrediction, and PCA were used to narrow down 113 suitable peptides, ultimately identifying 5 promising candidates (FW, FF, FPF, LPF, and VPF). The FW peptide demonstrated the best molecular docking results, with a binding energy of –9.32 kcal/mol and effective interactions with COX-2, highlighting its potential as a potent anti-inflammatory agent. This study provides a strong basis for the development of natural COX-2 inhibitors from marine organisms, contributing to the ongoing search for safer, bio-based anti-inflammatory drugs. GRAPHICAL ABSTRACT